The CARMA 3 mm survey of the inner 0.7^°× 0.4^° of the Central Molecular Zone. Issue 3 (26th September 2017) - Pound, Marc W.; Yusef-Zadeh, Farhad
Abstract: The Central Molecular Zone (CMZ) of the Galactic Centre has to date only been fully mapped at mm wavelengths with single-dish telescopes, with resolution about 30 arcsec (1.2 pc). Using Combined Array for Research in Millimeter-wave Astronomy (CARMA), we mapped the innermost 0.25 deg 2 of the CMZ over the region between −0.2° ≤ l ≤ 0.5° and −0.2° ≤ b ≤ 0.2° (90 × 50 pc) with spatial and spectral resolution of ∼10 arcsec (0.4 pc) and ∼2.5 km s −1, respectively. We provide a catalogue of 3 mm continuum sources and spectral line images of SiO(J = 2–1), HCO + (J = 1–0), HCN(J = 1–0), N2 H + (J = 1–0) and CS(J = 2–1), with velocity coverage V LSR = −200 to 200 km s −1 . To recover the large-scale structure resolved out by the interferometer, the continuum-subtracted spectral line images were combined with data from the Mopra 22-m telescope survey, thus providing maps containing all spatial frequencies down to the resolution limit. We find that integrated intensity ratio of I (HCN)/ I (HCO + ) is anticorrelated with the intensity of the 6.4 keV Fe K α, which is excited either by high-energy photons or low-energy cosmic rays, and the gas velocity dispersion as traced by HCO + is correlated with Fe K α intensity. The intensity ratio and velocity dispersion patterns are consistent with variation expected from the interaction of low-energy cosmic rays with molecular gas.